Study on human-SRL synchronized walking based on coupled impedance - Liu, Zihao; Xiang, Kui; He, Wutong; Gao, Xiang; Peng, Yaling; Pang, Muye (Frontiers in Neurorobotics, 2023)
Supernumerary robotic limbs (SRL) is a novel category of wearable robotics. Unlike prostheses (compensation for human limbs) and exoskeletons (augmentation of human limbs), SRL focuses on expanding human limbs and enhancing human activities, perception, and operation through the mutual collaboration of mechanical limbs and human limbs. The SRL of lower limbs are attached to the human waist, synchronized with the human walking in the forward direction, and can carry weight independently in the vertical direction. For the SRL to follow the human body movement steadily and cause the least amount of disturbance with human walking, the synchronization performance of the human-machine system during walking can be improved by studying the coupling dynamics of the human-SRL system. Since the human walking process is tough to model accurately and changes in the walking intention are tricky to predict, it is challenging for the SRL to collaborate well with the human body. To facilitate the research, this paper focuses on the relatively ideal working conditions: level road surface; no weight-bearing on the SRL; humans walking in a straight line without turning. Based on the passive dynamic walking theory and the human-SRL system model established by MIT, the modeling of the human-SRL coupling system is completed, and the optimal values of the stiffness and damping coefficient of the human-machine connection are obtained through numerical simulation. The wheel-legged SRL structure is designed, and the SRL control system is built. It is found that a better synchronization of the human-machine walking process can be achieved by configuring suitable spring and damping units in the human-machine connection part.